Effect of intermittent cold exposure on brown fat activation, obesity, and energy homeostasis in mice. - Yann Ravussin; Cuiying Xiao; Oksana Gavrilova; Marc L Reitman (PLoS ONE)
Homeotherms have specific mechanisms to maintain a constant core body temperature despite changes in thermal environment, food supply, and metabolic demand. Brown adipose tissue, the principal thermogenic organ, quickly and efficiently increases heat production by dissipating the mitochondrial proton motive force. It has been suggested that activation of brown fat, via either environmental (i.e. cold exposure) or pharmacologic means, could be used to increase metabolic rate and thus reduce body weight. Here we assess the effects of intermittent cold exposure (4°C for one to eight hours three times a week) on C57BL/6J mice fed a high fat diet. Cold exposure increased metabolic rate approximately two-fold during the challenge and activated brown fat. In response, food intake increased to compensate fully for the increased energy expenditure; thus, the mice showed no reduction in body weight or adiposity. Despite the unchanged adiposity, the cold-treated mice showed transient improvements in glucose homeostasis. Administration of the cannabinoid receptor-1 inverse agonist AM251 caused weight loss and improvements in glucose homeostasis, but showed no further improvements when combined with cold exposure. These data suggest that intermittent cold exposure causes transient, meaningful improvements in glucose homeostasis, but without synergy when combined with AM251. Since energy expenditure is significantly increased during cold exposure, a drug that dissociates food intake from metabolic demand during cold exposure may achieve weight loss and further metabolic improvements.